Implementation of PID-Based Temperature Control System for Helmet Dryers - Achmad Labib; Wanarti Rusimamto, Puput (INAJEEE (Indonesian Journal of Electrical and Electronics Engineering), 2023)
This research aims to design an automatic helmet dryer that uses PID-based temperature control to maintain a stable temperature at a setpoint of 45°C, especially in rainy season conditions that often make helmets wet and damp. A damp helmet has the potential to become a breeding ground for fungi and bacteria, as well as causing unpleasant odors and health problems. This tool controls the temperature using a PID controller with a BTS7960 driver module with temperature readings from a DHT22 sensor. The Ziegler-Nichols tuning method produces initial constant values Kp=7.64, Ki=0.1273, and Kd=114.6, but fine tuning is required to achieve the best constants Kp=100, Ki=1, and Kd=114.6. The test results show that the open face helmet can dry in 68 minutes with a final humidity of 38.9%, and the system response was 1,1% overshoot, 0 °C steady-state error, 246 seconds rise time, and 561 seconds settling time. Keywords: PID (Proportional-Integral-Derivative), Helmet Dryer, Ziegler-nichols.